Pannexin1 Channel Inhibitor (10panx) Protects Against Transient Focal Cerebral Ischemic Injury by Inhibiting RIP3 Expression and Inflammatory Response in Rats. (15th June 2020) - Wei, Ruili; Bao, Wangxiao; He, Fangping; Meng, Fangxia; Liang, Hui; Luo, Benyan
Highlights: Pannexin 1 channel inhibitor ( 10 panx) ameliorated focal ischemic brain injury. 10 panx reduced necroptosis related protein receptor-interacting protein 3 expression. 10 panx reduced the release of HMGB1 from neurons and inflammatory response. RIP3 was closely related with the release of HMGB1 from nucleus to cytoplasm. Abstract: Background: Recent studies have demonstrated that programmed necrosis (necroptosis) is a delayed component of ischemic neuronal injury and our previous study has shown that pannexin 1 channel is involved in cerebral ischemic injury and cellular inflammatory response. Here, we examined whether the pannexin 1 channel inhibitor, 10 panx, could reduce focal ischemic brain injury in rats by inhibiting cellular necroptosis and the associated inflammation. Male Sprague–Dawley rats were randomly divided into sham-operated, MCAO (transient middle cerebral artery occlusion) group, and 10 panx-treated groups. We investigated the effect of 10 panx by assessing infarct volume and neurological deficit. Further, we determined the potential mechanism using immunofluorescent staining, Western blotting, enzyme-linked immunosorbent assay (ELISA) and TUNEL assay. We demonstrated that 10 panx reduced infarct volume and alleviated neurological deficit in the MCAO injury model. 10 panx ameliorated post-ischemic neuronal death, but it did not reduce the TUNEL positive neurons and expression of cleaved-caspase3. In contrast, expression of necroptosis related protein receptor-interacting protein 3 (RIP3) was significantly decreased. Furthermore, 10 panx reduced the release of high mobility group box 1 (HMGB1) from neurons and inhibited microglial activation and secretion of pro-inflammatory factors. Immunent co-labeling of RIP3 with HMGB1 showed that RIP3 protein was closely related with the release of HMGB1 from nucleus to cytoplasm. Our data suggested that 10 panx treatment may ameliorate MCAO injury by reducing RIP3-mediated necroptosis, HMGB1 release and associated inflammatory response. RIP3 may play an important role in the release of HMGB1 and inflammation after stroke.